EFFECT OF ENZYME INHIBITORS AND ACTIVATORS ON THE MULTIPLICATION OF TYPHUS RICKETTSIAE : III. CORRELATION OF EFFECTS OF PABA AND KCN WITH OXYGEN CONSUMPTION IN EMBRYONATE EGGS - Greiff, Donald (The Rockefeller University Press, 1948)
A technique is described for measuring the oxygen uptake of embryonate eggs. Statistical analysis has shown that the method is reliable and accurate. Determinations were made on groups of 15 to 20 eggs, in order to average out individual biological variations. Reduction of the CO(2) tension and relative humidity to approximately zero previous to analysis has been found to be desirable. The oxygen consumption of normal and typhus-infected eggs, untreated and treated with agents previously found to inhibit or enhance rickettsial growth has been studied. Rickettsial infection caused a slight but significant increase in the rate of oxygen consumption on the 4th day after inoculation, followed by a rapid drop in the rate as the infection developed. The evidence suggests that low concentrations of rickettsial toxins may stimulate respiration, while higher concentrations depress respiration and lead eventually to embryonic death. PABA, which is rickettsiostatic, markedly increased the oxygen uptake of normal eggs, the effect appearing 4 days after injection and lasting for about 4 days. Thereafter, the rate fell below that of the untreated eggs. In typhus-infected eggs, PABA had similar effects, but the oxygen consumption reached much higher levels. A possible explanation of this fact is suggested. MABA and OABA, which are not rickettsiostatic, did not increase oxygen uptake; in fact they depressed cellular respiration moderately, OABA being more active in this way than MABA. These two compounds may compete with PABA for a position in some respiratory enzyme system. Potassium cyanide, which enhances rickettsial growth, caused, in concentrations not lethal to the embryos, a moderate drop in the oxygen consumption of normal eggs, the effect starting almost immediately after injection and lasting usually for 9 days. In infected eggs, its effect was more striking. It is probable that rickettsial toxins and KCN act synergistically to depress cellular respiration. When PABA and KCN were injected simultaneously, the stimulating effect of PABA on respiration predominated. The resulting level of oxygen consumption, though lower than that resulting from PABA alone, was still high enough to inhibit rickettsial growth. As far as our results go, they support the hypothesis that, within certain limits, rickettsial growth is inversely proportional to the respiratory rate of the host cells, regardless of the factors which determine that rate. It is not yet clear that PABA owes its rickettsiostatic action to its ability to increase cellular respiration, but this assumption seems reasonable as a working hypothesis. The respiratory mechanism in which PABA participates is not as yet known. Although PABA forms part of the folic acid molecule, folic acid itself, in concentrations corresponding to effective doses of PABA, did not increase cellular respiration or show rickettsiostatic action.